Oral Tofacitinib and Systemic Corticosteroids, Alone or in Combination, in Patients With Moderate-to-Severe Alopecia Areata: A Retrospective Study - Zhang, Wenxin; Li, Xiangqian; Chen, Baifu; Zhang, Jianzhong; Torres-Culala, Kara Melissa T.; Zhou, Cheng (Frontiers in Medicine, 2022)
Introduction Alopecia areata (AA) is an autoimmune hair loss mediated by CD8 + T cells. Treatment for moderate-to-severe AA is still challenging. Janus kinase inhibitors, such as tofacitinib, have been recently investigated as a promising treatment option for AA. Evidence on the combination use of oral tofacitinib and systemic corticosteroids (SCs) for AA is still lacking. Objective To compare the efficacy and safety of monotherapy of oral tofacitinib and SCs, as well as their combination in patients with moderate-to-severe AA. Methods Patients with moderate-to-severe AA, who have been treated with at least 3 months of monotherapy of tofacitinib or SCs, or in their combination, were included in this study. The efficacy and adverse events of these treatments were retrospectively analyzed. Results Sixty-one patients with moderate-to-severe AA were included in this study. There were 12 (66.7%) of 18 patients in the SCs group, 12 (60.0%) of 20 patients in the tofacitinib group, and 18 (78.3%) of 23 patients achieved SALT50, with no significant difference among the three groups. The ratio of patients who achieved SALT50 was significantly higher in patients with a short duration of current hair loss episode (≤2 years) than in those with a duration of current hair loss episode (>2 years) in all the three groups. There were 66.7% patients in the SCs group, 35.0% patients in the tofacitinib group, and 56.5% patients in the combined group that showed adverse effects. Conclusion Tofacitinib was an effective treatment for patients with moderate-to-severe AA, and it was more tolerated than SCs. A combination of tofacitinib and SCs may have higher efficacy than SCs alone. Efficacy significantly decreased in patients with a current episode of disease for more than 2 years.